Associations Between Inflammation and Cognitive Function in African Americans and European Americans. Issue 12 (December 2014) - Windham, B. Gwen; Simpson, Brittany N.; Lirette, Seth; Bridges, John; Bielak, Lawrence; Peyser, Patricia A.; Kullo, Iftikhar; Turner, Stephen; Griswold, Michael E.; Mosley, Thomas H.
<x xml:space="preserve">Abstract</x> Objectives To examine associations between specific inflammatory biomarkers and cognitive function in African Americans (AAs) and European Americans (EAs) with prevalent vascular risk factors. Design Cross‐sectional analysis using generalized estimating equations to account for familial clustering; standardized β‐coefficients, adjusted for age, sex, and education are reported. Setting Community cohort study in Jackson, Mississippi, and Rochester, Minnesota. Participants Genetic Epidemiology Network of Arteriopathy (GENOA)–Genetics of Microangiopathic Brain Injury (GMBI) Study participants. Measurements Associations between inflammation (high‐sensitivity C‐reactive protein (CRP), interleukin (IL)‐6, soluble tumor necrosis factor (TNF) receptor 1 and 2 (sTNFR1, sTNFR2)) and cognitive function (global, processing speed, language, memory, and executive function) were examined in AAs and EAs (N = 1, 965; aged 26–95, 64% women, 52% AA, 75% with hypertension). Results In AAs, higher sTNFR2 was associated with poorer cognition in all domains (global: −0.11, P = .009; processing speed: −0.11, P < .001; language: −0.08, P = .002; memory: −0.09, P = .008; executive function: −0.07, P = .03); sTNFR1 was associated with slower processing speed (−0.08, P < .001) and poorer executive function (−0.08, P = .008); higher CRP was associated with slower processing speed (−0.04, P = .024), and higher IL6 was associated with poorer executive function (−0.07, P = .02). In EA, only higher sTNFR1 was associated with slower processing speed (−0.05, P = .007). Associations were not found between cognition and sTNFR2, CRP, or IL6 in EA. Conclusion In a population with high vascular risk, adverse associations between inflammation and cognitive function were especially apparent in AAs, primarily involving markers of TNFα activity.